Seropositivity for Coxiella burnetii in Wild Boar (Sus scrofa) and Red Deer (Cervus elaphus) in Portugal - Humberto Pires; Luís Cardoso; Ana Patrícia Lopes; Maria da Conceição Fontes; Manuela Matos; Cristina Pintado; Luís Figueira; João Rodrigo Mesquita; Ana Cristina Matos; Ana Cláudia Coelho (Pathogens, 2023)
Q fever is caused by the pathogen Coxiella burnetii and is a zoonosis that naturally infects goats, sheep, and cats, but can also infect humans, birds, reptiles, or arthropods. A survey was conducted for the detection of antibodies against C. burnetii in a sample of 617 free-ranging wild ruminants, 358 wild boar (Sus scrofa) and 259 red deer (Cervus elaphus), in east–central Portugal during the 2016–2022 hunting seasons. Only adult animals were sampled in this study. Antibodies specific to C. burnetii were detected using a commercial enzyme-linked immunosorbent assay (ELISA; IDVet®, Montpellier, France) according to the manufacturer’s instructions. The seroprevalence of C. burnetii infection was 1.5% (n = 9; 95% confidence interval [CI]: 0.7–2.8%). Antibodies against C. burnetii were detected in 4/358 wild boar (1.1%; 95% CI: CI: 0.3–2.8%) and 5/259 red deer (1.9%; 0.6–4.5%). Results of the present study indicate that antibodies against C. burnetii were present in wild boar and red deer in Portugal. These findings can help local health authorities to focus on the problem of C. burnetii in wildlife and facilitate the application of a One Health approach to its prevention and control.